Combination of Vitex pseudo-negundo methanolic-extract with cisplatin can induce antioxidant activity and apoptosis in HeLa and Caski cells - Shiri Aghbash, Parisa; Sadri Nahand, Javid; Rahbar Farzam, Omid; Hosseini, Seyed Mohammad Reza; Bayat, Mobina; Entezari Maleki, Taher; Bannazadeh Baghi, Hossein (Frontiers in Pharmacology, 2024)
Background: Cisplatin-based chemotherapy as a common therapeutic regimen for cervical cancer patients, is becoming more and more ineffective due to high resistance. This urges the need for introducing novel metabolics such as botanical drugs with the capacity to increase the cisplatin effectiveness. In that regard, here we investigated the anticancer effects of the Cisplatin-Vitex pseudo-Negundo combination in cervical cancer cell lines.Method and Material: V. pseudo-Negundo fruits were dried and extracted methanolic fraction.The MTT assay was performed to evaluate cytotoxicity of both drugs in CaSki and HeLa cells.Then, apoptosis, ROS production, and cell cycling were assessed by flow cytometry assay in cells treated with V. pseudo-Negundo and Cisplatin and their combination. Also, the rate of cell migration and colony formation were measured, using wound healing and colony formation assay, respectively. Also, the expression level of related genes (CD133, BAX, BCL2, Casp-3/8/9, MMP-3) was evaluated using the RT-PCR method.The obtained results established that the V. pseudo-Negundo plant has medicinal properties to induce apoptotic and antioxidant signals. The combination treatment of methanol extraction and Cisplatin had a cytotoxic effect on cervical cancer cell lines (HeLa and CaSki) compared to monotherapy. Also, combination therapy resulted in an increased apoptosis rate and diminished ROS production in both CaSki and HeLa cell lines. Furthermore, V. pseudo-Negundo and Cisplatin combination therapy leads to cell cycle arrest in the G2-M and G0-G1 phase in HeLa and CaSki cell lines, respectively. Moreover, combination therapy decreased the colony formation and cell motility in both cell lines and upregulated caspases gene expression.The combination of V. pseudo-Negundo with Cisplatin therapy results in a significant anti-cancer and antioxidant effect compared to cisplatin, representing a promising candidate for future clinical investigations.